The Influence of Think Pair Share on Self-Efficacy and Oral English Commitment in the Grow Bareng Community - Raharja, I Made Samuel; Wahyuningsih, M B Rini (Widyagogik, 2024)
English is very important as it is used globally for communication and opens up career opportunities. In the Grow Bareng Community, speaking in English is still low, so the "think pair share" method is used to improve this ability. This study aims to examine the effect of this method on self-efficacy and oral English commitment. This study uses a quantitative approach with a Quasi-Experimental design and Pretest-Posttest Group Design. From a population of 60 students, 30 samples were selected using Cluster Sampling, divided into experimental and control groups with 15 participants each. The instruments used were Likert Scales, and data were analyzed using the Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov with SPSS version 24.00. The results of the study show: (1) There was a significant increase in oral English self-efficacy in the experimental group after using the "think pair share" method (p 0.05). (2) Oral English commitment also increased significantly in the experimental group (p 0.05). (3) Overall, there was a significant increase in self-efficacy and oral English commitment in the experimental group compared to the control group (p 0.05). In conclusion, the "think pair share" method is more effective in increasing self-efficacy and oral English commitment in the Grow Bareng Community.